Development of total hip joint replacement prostheses made by local material : an introduction - Tresna Priyana, Soemardi; Agri, Suwandi; Cholid, Badri; Anwar Soefi, Ibrahim; Sastra Kusuma, Wijaya; Siregar, J. P. (EDP Sciences, 2019)
Total Hip Joint Replacement Surgery is the procedure of surgical removal of cartilage in the hip joints damaged by disease osteoarthritis to replaced with artificial components. Total Hip Joint Replacement has been indicated to relieve pain in the pelvis due to degenerative joint disease. In Indonesia, this procedure has been practised, but due to the cost of expensive products resulting in limited only to upper classify patients. The high prices caused by importing prostheses products, the technological capabilities and the difficulty to meet the standards of medical devices. The regulation of the Minister of Health of the Republic of Indonesia Number 52, 2016 for standard rates in organising health services Health Assurance Program, explained that the action of these operations entered into the insurance claims BPJS program, but not for the prostheses. This paper discusses the introduction of the development of the hip joint prostheses made from a local material that’s SS 316L, PEEK and Ceramic Dental Stone. The result of this development is the product of the hip joint prostheses has a reasonable price with good quality so that it can become affordable for middle to lower patients.